Live-wire-based segmentation using similarities between corresponding image structures. - Matthias Färber; Jan Ehrhardt; Heinz Handels (Computerized medical imaging and graphics : the official journal of the Computerized Medical Imaging Society, 2007)
A live-wire-based segmentation method that exploits similarities of corresponding object contours is presented. The method accelerates the segmentation process transferring anchor points of segmented reference contours to unsegmented target slices automatically. The target contours are created using the live-wire algorithm trained by features of the reference contours. An automatic contour correction improves the segmentation. Only few user interactions with an intuitive contour editor are necessary. The evaluation using intra- and interpatient transfer shows that 51-73% of interaction time can be saved compared to normal live-wire preserving the segmentation quality.
Keywords: Algorithms; Germany; Humans; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Magnetic Resonance Imaging